Enhancing Cyclone Equipment with Smart Filters and Implementing SCADA for Environmental Management: A Literature Review (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Industrial air pollution remains a significant environmental and economic concern worldwide. Cyclone separators are commonly used for particulate matter removal, but traditional designs struggle with inefficiencies, particularly in handling fine particles and adapting to variable industrial conditions. This paper explores the integration of smart filtration technology and Supervisory Control and Data Acquisition (SCADA) systems to enhance cyclone equipment efficiency and environmental management. Smart filters utilize advanced sensor technology to optimize air purification dynamically, improving adaptability and energy efficiency. SCADA provides real-time monitoring, predictive maintenance, and automated control, reducing operational costs and increasing regulatory compliance. This study highlights the benefits of SCADA-integrated smart filtration in industries such as manufacturing, mining, and power plants, with a particular focus on Uzbekistan and other developing countries where air pollution control is becoming increasingly crucial. Additionally, this review discusses global case studies, including advancements in Germany, China, and the United States, to provide insights into best practices and implementation challenges. The findings suggest that AI-driven SCADA optimization and IoT-enabled filtration present future opportunities for enhanced industrial air quality management. Further research should focus on pilot studies and real-world implementation to validate these technologies’ effectiveness in various industrial settings.